2011
DOI: 10.1177/0885066610387984
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Physician Order Entry in the Critical Care Environment: A Review of Current Literature

Abstract: The implementation of health information technology (HIT) is accelerating, driven in part by a growing interest in computerized physician order entry (CPOE) as a tool for improving the quality and safety of patient care. Computerized physician order entry could have a substantial impact on patients in intensive care, where the potential for medical error is high, and the clinical workflow is complex. In 2009, only 17% of hospitals had functional CPOE systems in place. In intensive care unit (ICU) settings, CPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 42 publications
0
50
0
Order By: Relevance
“…Usability can be defined as the extent to which a product can be used by specific users to achieve specific goals, with effectiveness, efficiency, and satisfaction in a specific context of use 20 . Some of the commonly reported cpoe usability issues include an excessively complex and unintuitive user interface [21][22][23][24][25] , a cluttered or poorly organized display, lack of safeguards 21,24 , and inflexible or inefficient user interaction 21,[23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…Usability can be defined as the extent to which a product can be used by specific users to achieve specific goals, with effectiveness, efficiency, and satisfaction in a specific context of use 20 . Some of the commonly reported cpoe usability issues include an excessively complex and unintuitive user interface [21][22][23][24][25] , a cluttered or poorly organized display, lack of safeguards 21,24 , and inflexible or inefficient user interaction 21,[23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…For the preimplementation phase, interruptions were all numeric pages sent to all residents during the period of July [14][15][16][17][18][19][20][21][22][23][24][25][26][27]2008. For the post-implementation phase, interruptions were the e-mails sent directly to the team smartphones from the Web-based messaging system to all residents during the period of October 11-24, 2010.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] Other studies looking more broadly at patient information systems have identified problems caused by poor user interfaces that promoted errors in entry and retrieval of data, inflexible features forcing clinician workarounds, and technology designs that impeded clinical workflow. [21][22][23] These observations suggest that although many of the issues with clinical communication stem from the reliance on numeric paging, simply replacing pagers with newer technology may not solve the problems and can in fact create other unintended consequences.…”
mentioning
confidence: 99%
“…Health information technologies produce, manage and share health data in the health systems (25). Since health care is an information intensive business with huge volumes of data, multidisciplinary communication and team work are essential in healthcare.…”
Section: Discussionmentioning
confidence: 99%